2005
DOI: 10.1097/01.aids.0000194801.51422.03
|View full text |Cite
|
Sign up to set email alerts
|

Amount of lymphatic tissue fibrosis in HIV infection predicts magnitude of HAART-associated change in peripheral CD4 cell count

Abstract: The structure of lymphatic tissues is an important component of lymphatic tissue T-cell homeostasis. Collagen deposition in lymphatic tissues (common in HIV infection) disrupts the niche and limits the size of the resident CD4 cell population. In this report we show that a single measurement of lymphatic tissue collagen predicts the magnitude of recovery of the peripheral CD4 cell pool with HAART (P < 0.001). This suggests that collagen-targeted therapies might be of benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 10 publications
5
66
0
5
Order By: Relevance
“…On the other hand, collagen deposition, which impairs access to IL-7 on the FRC network and causes loss of the FRC network, itself an important source of IL-7, provides mechanisms for (a) depletion of both naive CD4 + and CD8 + T cells (38,39); (b) the continued high level of apoptosis in LTs while on HAART; and (c) the correlation between the extent of fibrosis of LTs before the initiation of HAART and the extent of restoration of naive CD4 T cells after long-term HAART (ref. 6 and Supplemental Figure 1B).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, collagen deposition, which impairs access to IL-7 on the FRC network and causes loss of the FRC network, itself an important source of IL-7, provides mechanisms for (a) depletion of both naive CD4 + and CD8 + T cells (38,39); (b) the continued high level of apoptosis in LTs while on HAART; and (c) the correlation between the extent of fibrosis of LTs before the initiation of HAART and the extent of restoration of naive CD4 T cells after long-term HAART (ref. 6 and Supplemental Figure 1B).…”
Section: Discussionmentioning
confidence: 95%
“…More recently, there has also been increasing evidence that fibrosis induced by immune activation damages lymphoid tissue (LT) niches, thereby contributing to T cell depletion and impaired immune reconstitution upon institution of antiretroviral drug treatment (1,2). In HIV-1 infection, fibrosis, measured as collagen deposition in LTs, strongly correlates with depletion of naive CD4 + T cells and inversely correlates with the extent of immune reconstitution after suppression of viral replication by antiretroviral therapy (2)(3)(4)(5)(6). In pathogenic SIV infection as well, collagen deposition in the early stage of SIV infection of rhesus macaques (Macaca mulatta; RMs) is associated with initial decreases in CD4 + T cells (7).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we found that the initial immune activation and T cell proliferation were actually comparable between SMs and RMs in terms of CD25 and Ki67 expression, although the fraction of effector (i.e., granzyme B-positive) T cells was higher in RMs during both acute and chronic infection. Interestingly, the most striking difference between the two species was the rapid and substantial resolution of this state of immune activation in SMs but not in RMs, an event that appears to be sufficient to protect SMs from subsequent CD4 ϩ T cell depletion, chronic T cell apoptosis, and LT niche-damaging fibrosis, i.e., all phenomena that contribute to disease progression during pathogenic HIV and SIV infections (19,(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…80 Indeed, local immune activation has been shown to be associated with fibrosis of the lymphoid architecture in peripheral lymph nodes, 42,84,85 which in turn predicts the degree of peripheral blood CD4 T-cell reconstitution after the initiation of HAART. 86 Importantly, recent findings suggest that fibrotic deposition of collagen also occurs in GI Peyer's patches even during the acute phase of the infection; the degree of architectural damage within Peyer's patches similarly predicts GI CD4 T-cell depletion after HAART. 87 Although HAART reduces GI immune activation, 80 the ability of the remaining but damaged lymphoid niche to support significant CD4 T-cell reconstitution may be permanently damaged.…”
Section: Haart and The Gastrointestinal Tractmentioning
confidence: 99%